Control Interno A Las Nóminas Y Su Incidencia En La Productividad De La Empresa Grupo Agriproduct S.A. De La Ciudad De Guayaquil Año 2023 - Riera Jiménez, Nery Aracelly (2025)
This research addresses a critical issue related to internal control applied to the payroll process, particularly its impact on organizational productivity. The general objective is to evaluate internal control and its incidence on the productivity of Grupo AGRIPRODUCT S.A., through the analysis of procedures implemented in the Human Resources area, regulatory compliance, and administrative efficiency. The study identifies weaknesses such as payment errors, unplanned overtime, payroll miscalculations, and informal hiring practices, all of which directly affect the company’s profitability. The research was carried out in the aforementioned company, with a study population composed of operational staff, administrative managers, and payroll control personnel. A qualitative–quantitative approach was used, with descriptive and analytical scope, applying methods such as inductive, deductive, historical-logical, and descriptive. Data collection involved surveys with operational staff, interviews with the plant manager and head of Human Resources, and a questionnaire based on COSO III internal control components. The study also explored the relationship between internal control and human talent management efficiency, and assessed compliance with labor regulations. The findings reveal structural weaknesses in internal procedures, negatively impacting operational performance and the organizational climate. Poor planning in payroll management, excess overtime, and non-compliance with labor laws result in additional costs and reduced operational efficiency.